RNA editing: changing the code in plants, animals and parasites - Hajduk, Stephen (Henry Stewart Talks, 2007)
Diversity of RNA editing, Nucleotide deaminase reactions, Enzyme mediated cascades, Small guiding RNA, Alternative RNA editing
Reviewed at 2016/01/19